Polymorphous low-grade neuroepithelial tumor of the young with FGFR3-TACC3 fusion mimicking high-grade glioma: case report and series of high-grade correlates - Golub, Danielle; Lynch, Daniel G.; Pan, Peter C.; Liechty, Benjamin; Slocum, Cheyanne; Bale, Tejus; Pisapia, David J.; Juthani, Rupa (Frontiers in Oncology, 2023)
Background: Polymorphous low-grade neuroepithelial tumor of the young (PLNTY) is a recently described entity that can mimic high-grade glioma (HGG) in histologic and molecular features; however, factors predicting aggressive behavior in these tumors are unclear. Methods: We present an indolent neuroepithelial neoplasm in a 59-year-old female with imaging initially suggestive of HGG, and a series of adult patients with HGG harboring FGFR3-TACC3 fusions are also presented for comparison. Results: Pathology in the case patient revealed low-grade cytomorphology, microcalcifications, unusual neovascularization, and a low proliferation index. The lesion was diffusely CD34+ and harbored FGFR3-TACC3 fusion and TERT promoter mutation. A diagnosis of PLNTY was therefore favored and the patient was observed with no progression at 15-month follow-up. In patients with HGG, molecular findings included IDH-wildtype status, absence of 1p19q codeletion, CDKN2A loss, TERT promoter mutations and lack of MGMT promoter methylation. These patients demonstrated a median 15-month overall survival and a 6-month progression-free survival. Conclusions: PLNTY is a rare low-grade entity that can display characteristics of HGG, particularly in adults. Presence of FGFR3-TACC3 fusions and other high-grade features should raise concern for a more malignant precursor lesion when a diagnosis of PLNTY is considered.